Skrining Fitokimia Ekstrak Etanol Biji Buah Tarap (Artocarpus odoratissimus) - Virda Putri Lestari; Sari Wijayanti; Faizal Mustamin (Politeknik Kaltara, 2024)
Tarap fruit (Artocarpus odoratissimus), also known as